Social Interaction Design for Social Media: The Case of Groupthink and Aggression - Tsikerdekis, Michail; Zlatuška, Jiří, 1957-; Masarykova univerzita. Katedra teorie programování (2013)
Social media today play an increasingly important role in computer science, the information technologies industry and society at large, changing people's everyday communication and interaction. The domain of social media encompasses a variety of services, such as social networking services, collaborative projects, microblogging services and even virtual social worlds and virtual game worlds. There are long established principles, guidelines, and heuristics that apply to social media design and are part of the foundations of human-computer interaction (HCI). For example, in interaction design two set of goals guide the design of systems, usability goals and user experience goals.However, current design and development frameworks are still ill-equipped for the ever-changing online world. Ironically, they fail to take into account the social dimension of social media software. Cracks in the social fabric of a community operating under social media software may have devastating effects, no
Social media today play an increasingly important role in computer science, the information technologies industry and society at large, changing people's everyday communication and interaction. The domain of social media encompasses a variety of services, such as social networking services, collaborative projects, microblogging services and even virtual social worlds and virtual game worlds. There are long established principles, guidelines, and heuristics that apply to social media design and are part of the foundations of human-computer interaction (HCI). For example, in interaction design two set of goals guide the design of systems, usability goals and user experience goals.However, current design and development frameworks are still ill-equipped for the ever-changing online world. Ironically, they fail to take into account the social dimension of social media software. Cracks in the social fabric of a community operating under social media software may have devastating effects, no
Vedoucí práce: Jiří Zlatuška
Dizertace (Ph.D.)--Masarykova univerzita, Fakulta informatiky, 2013
Keywords: sociální média; software; interakce člověk-počítač; výpočetní technika; human-computer interaction; computer science; computer technology; social media; software; disertace; dissertations